Phraseological Competence and Translation : A Pilot Study in an Undergraduate-Level Translation Program in Colombia (2023)
ABSTRACT: Phraseological competence is a concept that has been explored by phraseodidacts but it has not been studied in depth in Translation. This pilot study aims to identify features of the phraseological awareness of twelve translation students of a BA translation program in Colombia. The data was retrieved from an experiment in which the participants had to resolve a questionnaire and carry out three translation tasks (from English and French into Spanish) that involved the use of phraseological units. A Think-Aloud Protocol was applied to four of the participants who were asked to describe their translation process. The findings suggest that the degree of development of the participants’ phraseological competence differs among them, as well as in relation to the two source languages being analyzed, i.e., English and French. This study could be used as a starting point for further research leading to enhancing the syllabi of BA and MA Translator-training programs.